Redescription of Parapercis moki Ho and Johnson, 2013 (family Pinguipedidae), with its first fresh coloration information - Ho, Hsuan-Ching; Tang, Chi-Ngai; Chuang, Hsiang-Chieh (Zootaxa, 2022)
Two specimens of Parapercis moki Ho & Johnson were collected recently and detailed descriptions of their morphology and fresh coloration are provided. Its diagnosis is now revised as: band across head, six transverse bands on body and blade-like bar below eye; numerous small pores connected by canals forming about 9–10 vertical rows on cheek, opercle, and subopercle; scales on nape extending anteriorly to level of posterior margin of eyes; large spine on posteroventral corner of subopercle; very narrow interorbital space (1.7‒2.0% SL); 4 dorsal-fin spines, each spine progressively longer, last spine entirely connected by membrane to first dorsal-fin ray; four pairs of canine teeth anteriorly in lower jaw; and palatine teeth present, in two rows, and vomerine teeth stout, in two rows.